Growth response and production of two lady finger varieties by various type of organic fertilizers - ria anindi antika barus; chairani hanum; Rosita Sipayung (Universitas Sumatera Utara, 2018)
This research was conducted in Pembangunan street Subdistrict Medan Selayang, began from May to September 2016. This research used factorial randomized block design with two factors. The first factor was lady finger varieties were Red burgundy and Garibar. The second factor was application of organic fertilizer with four treatment (without organis fertilizer, compost 22,5g/10kg soil, vermicompost 30g/10kg soil, and chicken manure 75g/10kg soil). Garibar variety different on plant length, number of leaves, number of fruit, and fruit weight with Red burgundy. Chicken manure treatment can increase plant length, number of leaves, number of fruit, and fruit weight. Interaction between varieties and organic fertilizer treatment can increase plant length.